Italian Honeydew Honey Characterization by 1H NMR Spectroscopy - Dalila Iannone; Laura Ruth Cagliani; Roberto Consonni (Foods)
Honeydew honey represents a bee-derived product with different organoleptic characteristics and distinct properties with respect to floral honey. The market interest in honeydew honey has been growing in recent years due to its higher bioactive characteristics with respect to floral honey. The need for a deeper chemical characterization aimed to evaluate a possible botanical differentiation attracted the use of different analytical approaches. The present work aims to distinguish the botanical honeydew origin by using Nuclear Magnetic Resonance (NMR) spectroscopy and a multivariate approach. Two different data pretreatments have been considered to obtain the best sample discrimination. The saccharide content significantly affects the differentiation of the botanical variety consisting of fir, oak, citrus fruits, eucalyptus, and forest mainly by using a classification approach taking advantage of the Orthogonal Signal Correction filters. Notwithstanding the botanical diversity of the honeydew honey (HDH) samples, fir honeydew (F-HDH), oak honeydew (O-HDH), and eucalyptus honeydew (E-HDH) resulted always well discriminated among all the botanical varieties investigated, while citrus fruits honeydew (CF-HD) and forest honeydew (FO-HDH) did not. In particular, F-HDH resulted characterized by sucrose, erlose, maltose, maltotriose, maltotetraose, and melezitose, E-HDH resulted enriched in α, β-glucose and β-fructose in furanosidic form, and O-HDH enriched in β-fructose in furanosidic form, isomaltose.